2014
DOI: 10.1177/0021909614521414
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of Excluded Majorities in South Asian Parliaments: Women, Youth, and the Working Class

Abstract: This article provides a new perspective on parliamentary representation in South Asia, focusing on the collective under-representation of population majorities based on the macro-demographic categories of age, class, and gender. Situating this analysis within debates on descriptive representation, it presents the first comparative analysis of the contemporary demographic characteristics of members of parliament (MPs) in Bangladesh, Bhutan, India, Nepal, Pakistan, and Sri Lanka. Highlighting three major gaps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…Focusing on the representation of distinct age groups in 14 Asian countries, Joshi (2013) finds that PR fosters the representation of young adults. In a more restricted study, where he concentrates on characteristics of MPs in Bangladesh, Bhutan, India, Nepal, Pakistan, and Sri Lanka, Joshi (2015) confirms that PR positively affects the descriptive parliamentary representation of young adults 4 . Building on Joshi, we hypothesize that PR systems should trigger some higher representation of young adults.…”
Section: Theorymentioning
confidence: 90%
“…Focusing on the representation of distinct age groups in 14 Asian countries, Joshi (2013) finds that PR fosters the representation of young adults. In a more restricted study, where he concentrates on characteristics of MPs in Bangladesh, Bhutan, India, Nepal, Pakistan, and Sri Lanka, Joshi (2015) confirms that PR positively affects the descriptive parliamentary representation of young adults 4 . Building on Joshi, we hypothesize that PR systems should trigger some higher representation of young adults.…”
Section: Theorymentioning
confidence: 90%
“…The difference between these three age groups roughly associates an MEP with one distinct generation. Defining young parliamentarians as those aged 40 years and below also follows the recent literature on youth representation (see Joshi , ; Stockemer & Sundström ).…”
Section: Variables and Datamentioning
confidence: 99%
“…Earlier studies indicated that while relatively few women seek to hold political office (Iwanaga, 2008), they do create and implement a variety of cultural performance programs, which, for our study, may be useful in considering how TANs operate to raise awareness about environmental and gender-mainstreaming issues (Lai, 2010;Zeng, 2014). Furthermore, at a structural level, when the government does take an active role through quotas and proportional representation in electoral systems, women's agency is increased (Joshi, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%